Escola Sem Partido and the (real) problems of Brazilian education: an argumentative analysis - da Silva, Lucas Pereira (Redis: Revista de Estudos do Discurso, 2023)
In this article, we aim to discuss about a rhetorical-argumentative strategy of using epistemic argumentative instances to delegitimize the Motivating Circumstances that are constitutive of the polemics concerning Escola Sem Partido (ESP). We use a text representative of the position contrary to the ESP that aims to reframe the Practical Problem concerning the possible needs for action that become relevant in the social sphere of educational practices. For this, we assume the Argumentation Theory, in particular the notions of macrostructure and functional configuration of epistemic argumentation (Toulmin, 2003[1958]; Toulmin; Rieke; Janik, 1984[1978]) and practical argumentation (Fairclough; Fairclough, 2012; Gonçalves-Segundo, 2019). More punctually, we assume the studies on Polemics (Amossy, 2016; 2014), Critical Discourse Analysis (Fairclough, 2003; Gonçalves-Segundo, 2018), in addition to the cognitive-functional discussion on Epistemic Positioning (Gonçalves-Segundo, 2020b; Marín-Arrese, 2011). We identified an articulation that, firstly, seeks to question the validity of the reading of the current state of affairs in the discourse of favorable positions to the ESP and that, secondly, challenges the Motivating Circumstances that justify the ESP proposal and that fuel controversial dissent. This, in turn, results in an attempt to reframe the Practical Problem, in order to seek to focus on topics and themes considered of paramount importance for the maintenance of an educational system that needs improvement.